Determinan Keputusan Nasabah Menggunakan Produk Rahn Pada PT Pegadaian Syariah Sungai Liput - Liya Kartika; Muhammad Salman; Ainul Yusna Harahap (Jurnal Mahasiswa Akuntansi Samudra, 2023)
The research was conducted with the aim of finding out the influence of service quality, ease of transactions and estimated value on customers' decisions to use rahn products at PT Pegadaian Syariah Sungai Liput. This type of research is quantitative, the data source used is primary data. The population and sample for this research are Rahn customers at Pegadaian Sungai Liput, totaling 1,949 people as the population, and 96 respondents as the sample in this research which was calculated based on the Slovin formula. The data obtained was analyzed using SPSS (Statistical Package For Social Sciences) analysis techniques. The equation model analyzed is multiple linear regression analysis, classical assumption tests and hypothesis testing (T test, F test and coefficient of determination (R2). The research results show that partially service quality and estimated value have a significant positive effect on customers' decisions to use Rahn products, while ease of transaction has no effect on the customer's decision to use Rahn products. Simultaneously all independent variables, namely service quality, ease of transaction and estimated value together have a significant positive influence on the customer's decision to use Rahn products. Future researchers can use even more variable variables outside Variants of estimated value, costs and services influence customers' decisions to use rahn products at PT Pegadaian Sungai Liput. This is because, in this study, these three variables were only able to explain 34.1% of variations in customer decisions. This study has problem limitations. namely, the research only looks at the influence of service quality, ease of transactions, and estimated value as variables in revealing customers' decisions to use Rahn products. The research was conducted with the aim of finding out the influence of service quality, ease of transactions and estimated value on customers' decisions to use rahn products at PT Pegadaian Syariah Sungai Liput. This type of research is quantitative, the data source used is primary data. The population and sample for this research are Rahn customers at Pegadaian Sungai Liput, totaling 1,949 people as the population, and 96 respondents as the sample in this research which was calculated based on the Slovin formula. The data obtained was analyzed using SPSS (Statistical Package For Social Sciences) analysis techniques. The equation model analyzed is multiple linear regression analysis, classical assumption tests and hypothesis testing (T test, F test and coefficient of determination (R2). The research results show that partially service quality and estimated value have a significant positive effect on customers' decisions to use Rahn products, while ease of transaction has no effect on the customer's decision to use Rahn products. Simultaneously all independent variables, namely service quality, ease of transaction and estimated value together have a significant positive influence on the customer's decision to use Rahn products. Future researchers can use even more variable variables outside Variants of estimated value, costs and services influence customers' decisions to use rahn products at PT Pegadaian Sungai Liput. This is because, in this study, these three variables were only able to explain 34.1% of variations in customer decisions. This study has problem limitations. namely, the research only looks at the influence of service quality, ease of transactions, and estimated value as variables in revealing customers' decisions to use Rahn products.